Wonder and Encountering Nature in Transcendental Naturalism: A Reflection on Petersen’s Climate, God and Uncertainty - Sideris, Lisa H. (Zygon, 2025)
This commentary engages with and reflects on Arthur Petersen’s Climate, God and Uncertainty, particularly with how he treats wonder and encounters with nature. While Petersen’s book offers a painstakingly detailed and persuasive defense of transcendental naturalism that retains a privileged place for wonder, mystery, and uncertainty in the practice of science, more attention to the role of direct experience with nature and the awe-inspiring, ecologically-motivating potential of encounters with real creatures and real environments would be welcome. Suggestions are offered on how an elaboration on such encounters—how they happen, who can have them, how to encourage them more broadly—might fortify his account of wonder against the encroachment of scientistic appropriations of wonder that reduce it to knowledge of nature over and above nature itself.